Thermogravimetric kinetic analysis of in-situ catalytic pyrolysis of palm oil wastes with the presence of palm oil wastes ash catalyst - S W, Hii; B L F, Chin; Chung Loong, Yiin; F R S, Majing; Z A, Jawad; H Y, Lim; S, Yusup; M N, Acda; P, Unrean; E, Rianawati (2021)
The thermal degradation and kinetic analysis for oil palm frond (OPF) and oil palm trunk (OPT) with its ashes were investigated using thermogravimetric approach (TGA). OPF ash, OPT ash and its mixtures are used as a natural source of catalysts in the pyrolytic conversion of the palm oil wastes to bioenergy. The TGA experiments were conducted in a range of heating rates of 10-100 K/min from the temperature of 323 K to 1173 K. Coats-Redfern model is applied in this study to evaluate the activation energy (EA) and pre-exponential factor (A). The average EA values ranged 24.27-32.36 kJ.mol−1 and 41.42-46.10 kJ.mol−1 for pyrolysis of OPF and OPT respectively. Meanwhile, the average EA values ranged 24.27-31.06 kJ.mol−1 and 31.77-43.45 kJ.mol−1 for catalytic pyrolysis of OPF and OPT respectively.